Quality of neonatal resuscitation in Ethiopia: implications for the survival of neonates - Weldearegay, Haftom Gebrehiwot (BMC Pediatr, 2020)
BACKGROUND: Birth asphyxia accounts for one-quarter newborn deaths. Providing quality care service of neonatal resuscitation reduces neonatal mortality. However, challenges to providing quality neonatal resuscitation are not well investigated in Ethiopia. Hence, this study is conducted to assess the quality provision of neonatal resuscitation in Ethiopia. METHOD: We used data from the Ethiopian 2016 Emergency Obstetric Newborn Care survey, conducted in 3804 health facilities providing maternal and newborn health services. We described the quality of neonatal resuscitation services according to the structure, process and outcome triad of quality dimension. Data from registers and birth records for the last 12 months prior to the survey were extracted. In each facility, the three last eligible charts of resuscitated neonates were reviewed and the highest frequency of chart of resuscitated baby was considered to the analysis. Thus, a total of 555 charts were assessed. Logistic regression model was used to assess the relationship between the neonatal resuscitation processes, provider, facility and newborn characteristics with neonatal outcome at the time of discharge. RESULTS: The finding suggested that, around two-third, 364(65.6%) of the asphyxiated babies resuscitated by bag and mask type of neonatal resuscitation. Of the babies who had got neonatal resuscitation 463 (83.4%) survived. Resuscitated neonates with a gestational age of greater than 37 weeks and above (Adjusted Odds Ratio (AOR) =1.82; 95% Confidence Interval (CI) (1.09–3.04)), availability of priority equipment in health facilities for neonatal resuscitation (AOR = 1.24, 95% CI (1.09, 1.54)) and women who had 12 h and less duration of labor (AOR = 1.76; 95% CI (1.23, 3.13)) were the independent factors of survival of the neonate. CONCLUSION: Only half of the health facilities were ready for neonatal resuscitation (NR) in terms of priority equipment’s. However, eight out of ten babies survived after NR in Ethiopia. Gestational age, priority equipment for NR and duration of labor were determinants of survival of resuscitated neonates in Ethiopia. Therefore, the availability of priority equipment and attentive care and follow-up for premature neonates and those face prolonged labor need to be improved in Ethiopia.